Addressing overdose risk among unstably housed women in San Francisco, California: an examination of potential fentanyl contamination of multiple substances - Meredith C. Meacham; Kara L. Lynch; Phillip O. Coffin; Amanda Wade; Eliza Wheeler; Elise D. Riley (BMC, 2020)
Abstract Background Numerous reports have led to concerns that fentanyl is added to many street drugs as an adulterant, including to stimulants like cocaine and methamphetamine, and could increase risks for negative health outcomes. Methods We collected information regarding recent substance use through self-report and urine toxicology (confirmed with mass spectrometry) once a month for up to 6 monthly study visits from a probability sample of 245 women in San Francisco with a history of housing instability (2016-2019). We compared the presence of fentanyl metabolites with (1) the presence of metabolites for other substances and (2) self-reported past week substance use. Results Out of 1050 study visits, fentanyl metabolites were detected 35 times (i.e., at 3% of all study visits and among 19/245, or 8% of all women). In most but not all (91%, or 32/35) of these detected cases, heroin or opioid medication use was self-reported. Among women who reported cocaine or methamphetamine use, but did not use heroin or opioid medication, fentanyl was detected in only 1 of 349 cases (0.3%). In adjusted logistic regression, the presence of fentanyl metabolites was independently associated with (1) presence of opiate, heroin, and benzodiazepine metabolites, and (2) self-reported past week use of heroin and opioid medications. Fentanyl metabolite detection was not independently associated with cocaine or methamphetamine use. Conclusions The presence of fentanyl metabolites in this population was almost entirely among women who also reported using heroin or opioid pills. These data do not support the hypothesis that fentanyl is being routinely added to stimulants as an adulterant on a large scale in this region.